2013
DOI: 10.1111/nmo.12115
|View full text |Cite
|
Sign up to set email alerts
|

3‐D imaging, illustration, and quantitation of enteric glial network in transparent human colon mucosa

Abstract: We have established a useful approach for 3-D imaging, panoramic illustration, and quantitation of the enteric glia in the human colon mucosa to help characterize their roles with mucosal components in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…Intra-pancreatic ganglia and islet-ganglionic association in the human pancreas Next we used 3D histology with S100B (glial marker [37]) staining to characterise the intra-pancreatic ganglia and the glial network (Fig. 7a-g).…”
Section: Resultsmentioning
confidence: 99%
“…Intra-pancreatic ganglia and islet-ganglionic association in the human pancreas Next we used 3D histology with S100B (glial marker [37]) staining to characterise the intra-pancreatic ganglia and the glial network (Fig. 7a-g).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also shown that enteric glia in the myenteric plexus also receive a cholinergic innervation (35). That enteric glia are innervated along with neuronal and other non-neuronal colon, Liu et al showed that enteric glial processes form a continuous network in the lamina propria from the base of crypts extending up the mucosa to the crypt openings (48). Enteric glia are also in intimate contact with subepithelial myofibroblasts and the epithelial basement membrane.…”
Section: Role Of Enteric Glia In Gi Motility Disordersmentioning
confidence: 95%
“…However, the nature of this glial network in the human gut was not well understood. Recent findings using novel imaging methods reveal the very extensive nature of the distribution of mucosal enteric glia (48). Using optical clearing methods combined with high-resolution confocal microscopy in the human jci.org Volume 125 Number 3 March 2015 glial cells.…”
Section: Role Of Enteric Glia In the Mucosamentioning
confidence: 99%
“…Evaluation is needed of neuronal subtypes, as well as tracking of neurites in biopsies from people with bowel motility disorders. New 3D visualization approaches make this possible (121,122). Age-and region-specific control data are also needed, in order to know what ENS anatomy should be considered normal (123).…”
Section: Discussionmentioning
confidence: 99%